The Influence Of Sleep Patterns Based On The Sleep Disturbance Scale For Children (Sdsc) On The Height Of Children Aged 8-11 Years - Rosari Listiana; Annisa Nurul Arofah; Laksmitha Saktiono Safiitri; Hawin Nurdiana (Universitas Muhammadiyah Malang, 2022)
Sleep main an essential role in human development because growth hormone works best during the slow wave phase. About 20-30% of children have sleep problems. Children's bedtime has fallen more than usual over the last century, with school-age children having the most significant rate of change. This study aims to determine the effect of sleep patterns on height in children of SD Muhammadiyah 4 Malang aged 8-11 years. The cross-section method was used in this study. The sample in this study were all boys aged 8-11 years up to 98 children who met the inclusion criteria in SD Muhammadiyah 4 Malang. Data on height and weight were obtained from schools, and sleep patterns were obtained from questionnaires filled out by parents. Statistical analysis used Fisher's exact test with significance at p = 0.5. The results of this study did not show a significant effect between the child is sleeping position and height (p = 0.649). Most 8-year-old participants had poorer sleep patterns than their parents' height in the relevant categories. SD Muhammadiyah 4 Malang There is no significant effect between sleep patterns and height in children aged 8-11.